How do teachers design science learning media? A case study based on the Documentational Approach to Didactics - Fadhlan Muchlas Abrori (Postgraduate, University of Mataram, 2025)
The development of learning media conducted by teachers is strongly influenced by their past experiences and the resources they have learned. This study highlights this by using the Documentational Approach to Didactics. This study focuses on two aspects: Reflective Mapping of a Teacher’s Documentational Trajectory (RMDT) and Reflective Mapping of the Teacher’s Resource System (RMRS). RMDT highlights important events experienced by teachers that influence the media or work they produce. Besides, this study investigates how teachers design science learning media, drawing on their past experiences and available resources. The case study involved two elementary school teachers: one created a comic about environmental issues, and the other produced a video on biodiversity. Interviews with both teachers were analyzed using thematic analysis. Furthermore, RMRS emphasizes the resources that teachers utilize. From the case study analyzing two teachers, it is illustrated that RMDT and RMRS influence the media developed by teachers because they connect with the events and resources employed by teachers. For example, the first teacher had received training in both comic development and socioscientific content. The second teacher, who developed a video about biodiversity, had prior experience in video production and self-taught video editing, including the use of various video editing software